When The Walls Speak: A Screenplay Exploring The Struggles of A Chinese-Indonesian Daughter in Interracial Relationship - Gabrielle Putri Utomo; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This creative thesis tells the story of a daughter from a Chinese-Indonesian family who faces many struggles when she gets into an interracial relationship. The story is told through a screenplay in the genre of family drama and romance. This thesis also brings attention to the experiences of minority daughters in cross-cultural relationships, which is something that is rarely shown in Indonesian films. Using Murray Bowen’s Family Systems Theory (1966), the screenplay explores why the parents reject the relationship, what the daughter goes through because of it, and how she fights for their approval. The story shows that the parents’ rejection comes from their anxieties due to past traumas and cultural expectations, which leads to emotional tension, unresolved issues, and a broken relationship with their daughter. In the end, the thesis shows how the daughter stands up for her relationship by practicing differentiation of self while maintaining emotional independence and having honest conversations with her parents and with the help of her supportive partner.